2007
DOI: 10.1111/j.1447-0594.2007.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of idiopathic thrombocytopenic purpura by Chinese herbal medicine EK‐49 and ascorbic acid in an elderly patient developing chronic subdural hematoma

Abstract: Treatment of idiopathic thrombocytopenic purpura can present difficult therapeutic choices. An 88‐year‐old woman was admitted for treatment of a right subdural hematoma. She had a history of chronic thrombocytopenia, with follow‐up evaluations by a local physician. Platelet count on admission was 5 × 103/µL, with a high serum concentration of platelet‐associated immunoglobulin G. Bone marrow examination showed a marked increase in megakaryocytes. The patient was diagnosed with idiopathic thrombocytopenic purpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Shen-Cao granule is another traditional Chinese medicine with the ability to increase the number of PLTs [150] . Hirano et al also evaluated the efficacy of EK-49 and ascorbic acid in idiopathic ITP patients and suggested that while these agents could overcome thrombocytopenia, the conventional treatments such as prednisolone and azathioprine failed to recover low platelets [151] . Taken together, it seems that traditional Chinese medicine could be positioned as a pillar of thrombocytopenia treatment; however, it should not be forgotten that the safety and the tolerability of these agents have not been tested in COVID-19 patients yet.…”
Section: Thrombocytopenia-related Treatment In Covid-19mentioning
confidence: 99%
“…Shen-Cao granule is another traditional Chinese medicine with the ability to increase the number of PLTs [150] . Hirano et al also evaluated the efficacy of EK-49 and ascorbic acid in idiopathic ITP patients and suggested that while these agents could overcome thrombocytopenia, the conventional treatments such as prednisolone and azathioprine failed to recover low platelets [151] . Taken together, it seems that traditional Chinese medicine could be positioned as a pillar of thrombocytopenia treatment; however, it should not be forgotten that the safety and the tolerability of these agents have not been tested in COVID-19 patients yet.…”
Section: Thrombocytopenia-related Treatment In Covid-19mentioning
confidence: 99%
“…reported that KKT increased the platelet count by 31.7% and was clinically effective in 40.9% of 168 chronic idiopathic thrombocytopenic purpura patients . Hirano and Ueoka reported the case of an 88‐year‐old woman whose chronic subdural hematoma was successfully treated with KKT and ascorbic acid, which improved thrombocytopenia caused by idiopathic thrombocytopenic purpura . Yanase et al .…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the studies of Yang et al, 2022 reported that a combination treatment comprising of western medicine, TCM and high doses of ascorbic acid resulted in the most effective outcome in the treatment of COVID-19. Idiopathic t h r o m b o c y t o p e n i c p u r p u r a w a s successfully treated with a combination of ascorbic acid and TCM (Hirano et al, 2007).…”
Section: Moringa Oleifera and Ascorbic Acid In Traditional Chinese Me...mentioning
confidence: 99%